ZmHsp18 screened from the ZmHsp20 gene family confers thermotolerance in maize - Ming Xue; Yiwen You; Luyao Zhang; Jinming Cao; Mingliang Xu; Saihua Chen (BMC Plant Biology)
Abstract Heat stress has become one of the abiotic stresses that pose an increasing threat to maize production due to global warming. The Hsp20 gene family confers tolerance to various abiotic stresses in plants. However, very few Hsp20s have been identified in relation to maize thermotolerance. In this study, we conducted a comprehensive study of Hsp20s involved in thermotolerance in maize. A total of 33 maize Hsp20 genes (ZmHsp20s) were identified through scanning for a conserved α-crystalline domain (ACD), and they were categorized into 14 subfamilies based on phylogenetic analysis. These genes are distributed across all maize chromosomes and nine of them are in regions previously identified as heat-tolerance quantitative trait loci (hrQTL). These hrQTL-associated ZmHsp20s show variation in tissue-specific expression profiles under normal conditions, and seven of them possess 1–5 heat stress elements in their promoters. The integration of RNA-seq data with real-time RT-PCR analysis indicated that ZmHsp23.4, ZmHsp22.8B and ZmHsp18 were dramatically induced under heat stress. Additionally, these genes exhibited co-expression patterns with key ZmHsfs, which are crucial in the heat tolerance pathway. When a null mutant carrying a frame-shifted ZmHsp18 gene was subjected to heat stress, its survival rate decreased significantly, indicating a critical role of ZmHsp18 in maize thermotolerance. Our study lays the groundwork for further research into the roles of ZmHsp20s in enhancing maize’s thermotolerance.